Early efficacy evaluation of mesenchymal stromal cells (MSC) combined to biomaterials to treat long bone non-unions. (April 2020) - Gómez-Barrena, Enrique; Padilla-Eguiluz, Norma; Rosset, Philippe; Gebhard, Florian; Hernigou, Philippe; Baldini, Nicola; Rouard, Helène; Sensebé, Luc; Gonzalo-Daganzo, Rosa-María; Giordano, Rosaria; García-Rey, Eduardo; Cordero-Ampuero, José; et al.
Highlights: Bone healing efficacy was clinically observed in long bone non-union treated with MSC combined to bioceramics. Clinical and radiological healing of tibia, femur and humerus non-unions were compared and demographics analyzed. Investigations included the effect of bone, gender, smoking, and time since the initial fracture. Bone healing was better established 12 months after the operation. Abstract: Background and study aim: Advanced therapy medicinal products (ATMP) frequently lack of clinical data on efficacy to substantiate a future clinical use. This study aims to evaluate the efficacy to heal long bone delayed unions and non-unions, as secondary objective of the EudraCT 2011-005441-13 clinical trial, through clinical and radiological bone consolidation at 3, 6 and 12 months of follow-up, with subgroup analysis of affected bone, gender, tobacco use, and time since the original fracture. Patients and methods: Twenty-eight patients were recruited and surgically treated with autologous bone marrow derived mesenchymal stromal cells expanded under Good Manufacturing Practices, combined to bioceramics in the surgical room before implantation. Mean age was 39 ± 13 years, 57% were males, and mean Body Mass Index 27 ± 7. Thirteen (46%) were active smokers. There were 11 femoral, 4 humeral, and 13 tibial non-unions. Initial fracture occurred at a mean ± SD of 27.9 ± 31.2 months before recruitment. Efficacy results were expressed by clinical consolidation (no or mild pain if values under 30 in VAS scale), and by radiological consolidation with a REBORNE score over 11/16 points (value of or above 0.6875). Means were statistically compared and mixed models for repeated measurements estimated the mean and confidence intervals (95%) of the REBORNE Bone Healing scale. Clinical and radiological consolidation were analyzed in the subgroups with Spearman correlation tests (adjusted by Bonferroni). Results: Clinical consolidation was earlier confirmed, while radiological consolidation at 3 months was 25.0% (7/28 cases), at 6 months 67.8% (19/28 cases), and at 12 months, 92.8% (26/28 cases including the drop-out extrapolation of two failures). Bone biopsies confirmed bone formation surrounding the bioceramic granules. All locations showed similar consolidation, although this was delayed in tibial non-unions. No significant gender difference was found in 12-month consolidation (95% confidence). Higher consolidation scale values were seen in non-smoking patients at 6 ( p  = 0.012, t -test) and 12 months ( p  = 0.011, t -test). Longer time elapsed after the initial fracture did not preclude the occurrence of consolidation. Conclusion: Bone consolidation was efficaciously obtained with the studied expanded hBM-MSCs combined to biomaterials, by clinical and radiological evaluation, and confirmed by bone biopsies, with lower consolidation scores in smokers.